2019
DOI: 10.1177/0269215519893096
|View full text |Cite
|
Sign up to set email alerts
|

Does trunk muscle training with an oscillating rod improve urinary incontinence after radical prostatectomy? A prospective randomized controlled trial

Abstract: Objective: To investigate the effect of a new therapeutic approach, using an oscillating rod to strength the pelvic floor and deep abdominal musculature and to speed up recovery of continence after radical prostatectomy. Design: Prospective randomized controlled clinical trial. Setting: Inpatient uro-oncology rehabilitation clinic. Subjects: Ninety-three (intervention group (IG)) and ninety-one patients (control group (CG)) with urinary incontinence after prostatectomy were examined. Intervention: All patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
1
12
0
1
Order By: Relevance
“…They found a moderate inverse correlation has been identified between muscle power and 24-hour pad test in APFMT (14). Subsequently, several trials published their findings of APFMT compared to CPFMT (15)(16)(17)(18). Our study indicated that APFMT and CPFMT were feasible owing to low attrition rate and no adverse events reported.…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…They found a moderate inverse correlation has been identified between muscle power and 24-hour pad test in APFMT (14). Subsequently, several trials published their findings of APFMT compared to CPFMT (15)(16)(17)(18). Our study indicated that APFMT and CPFMT were feasible owing to low attrition rate and no adverse events reported.…”
Section: Discussionsupporting
confidence: 51%
“…No adverse events were reported in all included studies (13)(14)(15)(16)(17)(18). Patients receiving APFMT had a similar attrition rate to those receiving CPFMT (18/236 vs. 22/282, P=0.61).…”
Section: Apfmt Versus Cpfmtmentioning
confidence: 91%
See 3 more Smart Citations